Perancangan Sistem Informasi Pelayanan Sosialisasi Masyarakat BPBD Berbasis Web untuk Efisiensi Pengelolaan Data (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This study aims to design and develop a web-based information system for managing socialization services at the Regional Disaster Management Agency (BPBD) of Banyuwangi Regency. The existing problem is that socialization data management is still carried out using Google Forms and Google Sheets separately, which causes difficulties in integration, monitoring, and reporting activities. This study uses the Research and Development (R&D) method with the Waterfall software development model which includes the stages of needs analysis, design, implementation, testing, and system maintenance. The results show that the developed web-based information system allows input, storage, and presentation of socialization activity data in real-time in one integrated dashboard. This system can simplify the process of monitoring, evaluation, and preparation of activity reports, while increasing the efficiency and accuracy of data management. With this system, BPBD Banyuwangi is expected to provide socialization services to the community in a more effective, transparent, and timely manner.